2014
DOI: 10.1016/j.neuroscience.2013.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Novel Vitamin K analogs suppress seizures in zebrafish and mouse models of epilepsy

Abstract: Epilepsy is a debilitating disease affecting 1-2% of the world’s population. Despite this high prevalence, 30% of patients suffering from epilepsy are not successfully managed by current medication suggesting a critical need for new anti-epileptic drugs (AEDs). In an effort to discover new therapeutics for the management of epilepsy, we began our study by screening drugs that, like some currently used AEDs, inhibit HDACs using a well-established larval zebrafish model. In this model, 7-day post fertilization (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…Of particular interest is Menadione, or Vitamin K3. Interestingly, a review of the literature produces evidence that Vitamin K3 acts to inhibit HDAC6, [ 24 ], suggesting that this connection has been correctly identified by QUADrATiC.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Of particular interest is Menadione, or Vitamin K3. Interestingly, a review of the literature produces evidence that Vitamin K3 acts to inhibit HDAC6, [ 24 ], suggesting that this connection has been correctly identified by QUADrATiC.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In an effort to identify novel therapeutics for treatment in humans, many high-throughput chemical screens using the zebrafish model have been aimed at modulating ototoxicity (Esterberg et al, 2013), seizures (Baraban et al, 2013; Rahn et al, 2014), and cancer (Lee et al, 2007; Nguyen et al, 2012). Work from Leonard Zon and colleagues at Harvard Medical School provides an excellent proof of concept on how to translate high-throughput zebrafish screens from the tank to the bedside.…”
Section: High-throughput Screening Is Practical In a Vertebrate Modelmentioning
confidence: 99%
“…With these cells, it was found that the mitochondrial permeability transition pore inhibitor, cyclosporine A, as well as carnitine (fatty acid transport) and N-acetylcysteine (antioxidant), could prevent valproic acid-induced toxicity. We have also been testing new and old chemical compounds on Polg mutant zebrafish, which takes advantage of an in vivo vertebrate animal model that can be treated like cells in a dish due to its very small size (Garcia et al 2016; Rahn et al 2014; Rahn et al 2015). …”
Section: Promoting Mtdna Stabilitymentioning
confidence: 99%